Teacher Empowerment: Insights on the Enhancement of Teacher Capabilities Leadership Practices and Teacher Empowerment - Rex U. Celosia; Maria Liesle A. Dopeno; Jay L. Galimpin (Future Science / FSH-PH Publications, 2026)
Teacher empowerment is essential to enhance learning outcomes as it directly influences classroom dynamics and educational effectiveness. Thus, this study investigated the teacher empowerment towards enhanced capability among public school teachers in Tagbilaran City and Bohol Divisions for the school year 2023-2024. It employed mixed method approach, particularly convergent parallel design. In the quantitative strand, the study surveyed 280 administrators and 369 public school teachers. In the qualitative strand, an in-depth interview was conducted to ten (10) participants. Results revealed that school heads had a more positive view of teacher empowerment than the teachers themselves, a difference confirmed by statistical analysis. Both groups rated professional growth and self-efficacy domains favourably, but teachers saw their decision-making power as moderate. Factors like leadership, trust, support, and collaboration enhanced empowerment, while micromanagement, limited autonomy, and poor communication hindered it. The study revealed a gap in how the two groups viewed decision-making processes, likely influenced by collaborative program development and tensions around teacher independence within curriculum guidelines. High professional growth ratings aligned with teachers' focus on reflection and effective strategies. Interestingly, qualitative data highlighting teacher collaboration and innovation suggests why teachers may have rated their overall impact lower than school heads did. Recommendations were given to enhance teachers’ empowerment.